Identifying skylines in dynamic incomplete database - Babanejaddehaki, Ghazaleh; Ibrahim, Hamidah; Udzir, Nur Izura; Sidi, Fatimah; Dehaki, Ghoncheh Babanejad; Aljuboori, Ali Amer Alwan (WSEAS Press, 2015)
Nowadays in database systems finding the best results that meet the preferences of users is the most important issue. Skyline queries will present the data items that are not being dominated by the other items in a database. Most of the operations assume the database is complete which means there are no missing values in the database dimensions. In reality, databases are not complete especially for multidimensional database. Missing values have a negative effect on finding skyline points. It changes the native of dominance relation, leads to cyclic dominance and unsatisfying the transitivity property of skylines. This problem becomes more severe in dynamic database in which new items are inserted or items are deleted or updated from the database. Besides, most of the works that handled the incomplete issue assumed that items are static. In this paper we propose the new approach which finds the most relevant data items that meet user’s preferences for dynamic incomplete databases.